2012
DOI: 10.1089/neu.2011.1930
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Brain-Derived Neurotrophic Factor Gene Influence Memory and Processing Speed One Month after Brain Injury

Abstract: Brain-derived neurotrophic factor (BDNF) plays a role in cognition, as well as neural survival and plasticity. There are several common polymorphisms in the BDNF gene, one of which (rs6265) is an extensively studied non-synonymous coding polymorphism (Val66Met) which has been linked to cognitive performance in healthy controls and some clinical populations. We hypothesized that the Met allele of rs6265 would be associated with poorer cognitive performance in individuals with mild-to-moderate traumatic brain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 30 publications
3
61
1
2
Order By: Relevance
“…Emerging technologies that could improve prognostication in mTBI include proteomic biomarkers, [31][32][33] genetic factors, [34][35][36] and improved imaging biomarkers, including magnetic resonance imaging. 37 Additionally, prediction models for mTBI may require moresensitive and -specific outcome measures beyond the GOS-E.…”
Section: Predictors Of Unfavorable Outcomementioning
confidence: 99%
“…Emerging technologies that could improve prognostication in mTBI include proteomic biomarkers, [31][32][33] genetic factors, [34][35][36] and improved imaging biomarkers, including magnetic resonance imaging. 37 Additionally, prediction models for mTBI may require moresensitive and -specific outcome measures beyond the GOS-E.…”
Section: Predictors Of Unfavorable Outcomementioning
confidence: 99%
“…110,115 The APOE genotype is not neces sarily a non-modifiable risk factor for concussion recovery: therapies being developed for AD include drugs that modify the interaction between the ApoE4 protein and Aβ, which might also be applicable to paediatric concussion. 116,117 Other genetic risk factors The Val66Met polymorphism in the gene encoding brain-derived neurotrophic factor has been linked to better outcomes after mTBI, 118 but worse outcomes after focal penetrating brain injury. 119 Polymorphisms in genes involved in dopaminergic signalling may also help to account for the wide range of TBI outcomes.…”
Section: Apolipoprotein Ementioning
confidence: 99%
“…Research has shown that some of these elements may guide regrowth of damaged neurons in developed organisms (Deister and Schmidt, 2006). One such element is brain-derived neurotrophic factor (BDNF) that seems to profit brain recovery after TBI (McAllister et al, 2012;Rostami et al, 2011). The expression of plasticity genes such as Bdnf, Homer1a and Fos or of their protein product is increased in the hippocampus and cortex during the first hours after mTBI (Abrous et al, 1999;Colak et al, 2012;Crack et al, 2009;Hicks et al, 1999).…”
Section: Introductionmentioning
confidence: 99%